2017
DOI: 10.1038/nrrheum.2017.42
|View full text |Cite
|
Sign up to set email alerts
|

Dietary factors in rheumatic autoimmune diseases: a recipe for therapy?

Abstract: Today, we are facing a new era of digitization in the health care system, and with increased access to health care information has come a growing demand for safe, cost-effective and easy to administer therapies. Dietary habits have a crucial influence on human health, affecting an individual's risk for hypertension, heart disease and stroke, as well as influencing the risk of developing of cancer. Moreover, an individual's lifestyle choices can greatly influence the progression and manifestation of chronic aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 158 publications
0
48
0
2
Order By: Relevance
“…An expression of these receptors promotes prolonged residence of macrophages in bloodstream and the development of foam cells due to increased receptor-mediated oxLDL uptake. A review summarizes the connection between dietary nutrients and immune function [35,60] and we elaborate on some of the mechanisms by which dietary lipids influence immune function at the cellular level.…”
Section: Fatty Acids Influence Lymphocyte Proliferation and Cytokine mentioning
confidence: 99%
“…An expression of these receptors promotes prolonged residence of macrophages in bloodstream and the development of foam cells due to increased receptor-mediated oxLDL uptake. A review summarizes the connection between dietary nutrients and immune function [35,60] and we elaborate on some of the mechanisms by which dietary lipids influence immune function at the cellular level.…”
Section: Fatty Acids Influence Lymphocyte Proliferation and Cytokine mentioning
confidence: 99%
“…Bo Vahlquist (1909‐1978), a renowned pediatrician once said “In all mammalian species the reproductive cycle comprises both pregnancy and breast‐feeding: in the absence of latter, none of these species, man included, could have survived” . Diet is one of the most important environmental exposures in early life . Currently, the World Health Organization recommends that infants should be exclusively breastfed up to 6 months of age and continue with a partial pattern until the infant is at least 2 years old .…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this increase has been attributed partially to the hygiene hypothesis . However, there is also rising evidence that dietary factors contribute to the pathogenesis of several autoimmune diseases . In this regard, recent studies in the mouse have shown that animals fed a HSD are likely to develop more severe autoimmune manifestations …”
Section: Introductionmentioning
confidence: 99%